Extraction of polyphenols from Clinacanthus nutans Lindau medicinal plant using solvent-free microwave extraction (SFME) - Mohd Tahar, Mohamad Azrul Sofi (2017)
In general, this research is about the extraction of polyphenols from Clinacanthus nutans Lindau (C. nutans) which used Solvent-Free Microwave Extraction (SFME). In Malaysia, C. nutans is well-known with their high polyphenols content and medicinal purposes in traditional treatment such as fever, snake bites, anti-herpes, anti-inflammatory properties and etc. In previous extraction, conventional methods have been used to extract the polyphenols content such as maceration and soxhlet extraction which consumed a longer time and high amount of solvent which may toxic or poison the polyphenols content. Therefore, several methods have been introduced to reduce the consumption of solvent and extraction time which are Supercritical Fluid Extraction (SFE) and Microwave-Assisted Extraction (MAE). However, this method still used solvent to extract. Thus, Solvent-Free Microwave Extraction is conducted to extract which the extraction is without consumed any solvent or water. The extracts are analysed by Folin-Ciocalteu colorimetric method and aided by UV-Vis Spectrometer in order to achieve one of the objectives which is to determine the total phenols content (TPC). Furthermore the effect on extraction is investigated: microwave power and extraction time. In order to explain more the efficiency in extraction of the polyphenol content, extraction temperature and energy absorbed during the exposure to the microwave radiation have been studied and analysed. Among the results, the best result which indicated higher total phenol content extracted by SFME which used microwave power, 240 W and extraction time, 1 min, is 1.4610 mg GAE/g DS with energy absorbed, 0.90 kJ. The polyphenols yield is depended on the microwave power and extraction time as well as extraction temperature and energy absorbed. The higher microwave power and longer extraction time may lead to the degradation of polyphenols due to high extraction temperature.